2018
DOI: 10.1002/jbm.a.36379
|View full text |Cite
|
Sign up to set email alerts
|

The influence of matrix stiffness on the behavior of brain metastatic breast cancer cells in a biomimetic hyaluronic acid hydrogel platform

Abstract: Breast cancer brain metastasis marks the most advanced stage of breast cancer no longer considered curable with a median survival period of ∼4-16 months. Apart from the genetic susceptibility (subtype) of breast tumors, brain metastasis is also dictated by the biophysical/chemical interactions of tumor cells with native brain microenvironment, which remain obscure, primarily due to the lack of tunable biomimetic in vitro models. To address this need, we utilized a biomimetic hyaluronic acid (HA) hydrogel platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…In accordance, we also found a significant enrichment of the BCSC markers CD44, CD49f, P-cadherin, EpCAM, and ALDH1 in human breast cancer brain metastasis when compared with unmatched primary tumors previously analyzed by our group [34,41,42,51]. This clearly indicates that there is an imbalance of adhesion/stem cell molecules that lead to a modification in malignant and colonization properties in distant sites, such as the brain [18,[52][53][54][55][56][57]. However, more importantly, our study revealed an enriched stem cell profile defined by the simultaneous expression of 3-5 of these BCSC markers, which we defined as a BR-BCSC signature.…”
Section: Discussionsupporting
confidence: 85%
“…In accordance, we also found a significant enrichment of the BCSC markers CD44, CD49f, P-cadherin, EpCAM, and ALDH1 in human breast cancer brain metastasis when compared with unmatched primary tumors previously analyzed by our group [34,41,42,51]. This clearly indicates that there is an imbalance of adhesion/stem cell molecules that lead to a modification in malignant and colonization properties in distant sites, such as the brain [18,[52][53][54][55][56][57]. However, more importantly, our study revealed an enriched stem cell profile defined by the simultaneous expression of 3-5 of these BCSC markers, which we defined as a BR-BCSC signature.…”
Section: Discussionsupporting
confidence: 85%
“…After incubating at 37°C for approximately 30 min to form hydrogels, EMEM or Neurobasal‐A medium was added depending on the cell type and the medium was changed every day. For another experimental setup, integrin‐binding peptide (RGD; Anaspec) was presented to the cells in a matrix‐bound form by incorporating it into the HA methacrylate backbone through Michael‐type addition reaction as previously described (Ananthanarayanan et al, ; Narkhede et al, ). After functionalizing gel precursor solution with RGD for 3 hr, single glioblastoma cells were added to it and hydrogels were prepared similarly as described above.…”
Section: Methodsmentioning
confidence: 99%
“…HA was methacrylated adapting the procedure previously described (Ananthanarayanan, Kim, & Kumar, 2011;Narkhede, Crenshaw, Manning, & Rao, 2018). Briefly, 1 wt% HA of molecular weight 60 kDa (66-99 kDa; Lifecore Technologies) was subjected to a six-fold molar excess of methacrylic anhydride (Sigma Aldrich) while maintaining the pH above 8 throughout the reaction using 5 M NaOH solution at 4°C.…”
Section: Glioblastoma Cell Culture In 3d Ha Hydrogelsmentioning
confidence: 99%
“…(C) Block copolymer micelle nanolithography (BCMN) with thiol-end HA (atomic force microscopy image of a glass surface covered with gold nanodots); and (D) microcontact printing with side-on immobilization of HA[99]. (E) 3D hydrogels for cell encapsulation, with tuned mechanical properties (varying the HA M w , the crosslinking degree, and/or the HA blended with other biocompatible materials)[58]. All the images were used and adapted, with permission, from[58,[97][98][99].…”
mentioning
confidence: 99%
“…(E) 3D hydrogels for cell encapsulation, with tuned mechanical properties (varying the HA M w , the crosslinking degree, and/or the HA blended with other biocompatible materials)[58]. All the images were used and adapted, with permission, from[58,[97][98][99]. Abbreviations: LYVE, Lymphatic vessel endothelial receptor for hyaluronan; RHAMM, receptor for hyaluronan-mediated motility; TLR, toll-like receptor.…”
mentioning
confidence: 99%